From Static Stability to Dynamic Gait Governance: Differential Effects of Adapted Physical Activity and Tango-Based Therapy on Walking Distance and Plantar Load Redistribution in Parkinson’s Disease - Raffaella R. R. Marzovillo; Gabriella D’Orsi; Paride Vasco; Giuseppe Cartagena; Donato Melchionda; Natalia Forte; Giuseppe Cibelli; Anna A. Valenzano (Sports, 2026)
Gait and balance impairments in Parkinson’s disease (PD) severely compromise mobility and independence. This exploratory randomized pilot study evaluated a multimodal Adapted Physical Activity (APA) protocol, a tango-based program (Riabilitango®, RT), and standard care regarding walking distance, static postural stability, joint range of motion, and plantar-load redistribution. Twenty-seven participants with PD (Hoehn and Yahr 1–3) were allocated to APA (n = 10), RT (n = 10), or Control (n = 7). The active groups completed 24 supervised sessions over 12 weeks. Static postural stability and treadmill-based walking distance were evaluated at baseline and post-intervention. Both active interventions showed favorable static sway profiles compared to Control, though between-group differences were non-significant. Crucially, APA demonstrated a significantly greater post-intervention improvement in walking distance than RT and Control. Exploratory analyses linked APA walking gains to adaptations in joint mobility and plantar-load redistribution. In conclusion, multimodal APA showed the clearest functional signal for improving walking distance in PD, whereas Riabilitango® offered a complementary profile focused on sensorimotor integration and balance. These preliminary pilot findings warrant confirmation in larger prospective trials.